Meshing State and Force Analysis of the Crown Gear Coupling with Inter-axial Tilt Angle - Wei Jiaqi; Zhang Kailin; Yao Yuan (Jixie chuandong)
In order to analyze the additional moment and the characteristic of the meshing tooth when the inter- axial tilt angle exist in the crown gear coupling,the geometric analysis method is taken to calculate the minimum circumferential clearance between the teeth,which can be recognized as the requirement of teeth meshing. The position of the contact point and the clearance between the teeth surface on the different inter- axial tilt angle are analyzed. According to the Hertz contact theory,the osmolality and contact force of the tooth surface contact point can be calculated,so that the additional moment of the coupling can be calculated. The result shows that the inter- axial tilt angle of gear coupling shafts due to inhomogeneous distribution of the mashing point in the circumferential direction,and the variation range turns larger when the inter- axial tilt angle and the tooth surface crowning radius get larger. The relative contact force coefficient is defined to reflect the asymmetry level. When the turning moment is 4000 N·m and the inter- axial tilt angle is 1. 1°,the relative contact force coefficient is about 3. 3 and the contact teeth pairs is about 2 /3 of all. The movement of the meshing point can due to the additional moment,so that the coupling will roll about the direction which vertical to the axle,the additional moment takes about 6% 15% of the turning moment,and it will increase with the inter- axial tilt angle.